Wind erosion and its ecological effects on soil in the northern piedmont of the Yinshan Mountains. (September 2021) - Wu, Xiaoguang; Fan, Jiaqi; Sun, Lin; Zhang, Hongfei; Xu, Yan; Yao, Yunfeng; Yan, Xudong; Zhou, Jian; Jia, Yushan; Chi, Wenfeng
Highlights: The spatiotemporal dynamics of wind erosion from 1990 to 2015 were explored. Soil nutrients were lost rapidly due to wind erosion but recovered slowly. Further ecological projects were indispensable to promote sustainable development. Abstract: Soil erosion by wind is a serious problem that threatens ecological security and damages the ecological environment, thereby hindering the sustainable development of agriculture and animal husbandry in arid and semiarid areas. Using the northern piedmont of the Yinshan Mountains in the Inner Mongolia Autonomous Region of China as a study area, this study explores the spatiotemporal variation in soil loss by wind erosion and its impact on soil nutrients from 1990 to 2015. Various approaches, including remote sensing technology, the revised wind erosion equation model, the fallout cesium-137 tracing technique, and the geographic information system (GIS) spatial analysis technique, were jointly used in the present study. From 1990 to 2015, the soil loss by wind erosion obviously decreased, with a slope of −0.59 t/ha/a, in the study area. Affected by factors such as regional topography and wind direction, the wind erosion modulus is high in the northwest and low in the south and southeast of the northern piedmont of the Yinshan Mountains. The soil nutrient content decreased overall from 1990 to 2015, including a severe loss from 1990 to 2005 and a relatively low nutrient enrichment from 2005 to 2015. The decline in the sand-dust storm frequency and wind speed protected the soil from wind erosion. Implementing ecological management projects has played an important role in slowing wind erosion and enhancing the regional ability to resist wind erosion and fix sand. To improve soil quality and the regional ecological environment, ecological restoration projects should be further promoted in the study area.